Pengaruh Leverage, Capital Intensity, dan Corporate Social Responsibility terhadap agresivitas pajak - Sebastian Soelistiono; Priyo Hari Adi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
Tax aggressiveness is the company's effort to reduce the tax burden. The decrease in tax is due to differences in opinion between the company and the government. Corporate tax aggressiveness can be caused by leverage, capital intensity, and corporate social responsibility. This study aims to determine the effect of leverage, capital intensity, and corporate social responsibility on tax aggressiveness. The research was conducted on mining companies listed on the Indonesia Stock Exchange (IDX). There are 19 companies as the research sample with a total of 57 data. The analytical technique used in this research is multiple linear regression analysis. The results showed that leverage did not affect tax aggressiveness, due to the use of debt and commitment to creditors. Capital intensity has a significant effect on tax aggressiveness, because mining companies consider the costs and benefits of investing in fixed assets. Corporate social responsibility also has a significant effect on tax aggressiveness, because the goal is to improve the impact of activities accompanied by a reduction in the amount of mining company taxes. Related to further research, it can increase the research period to expand sample selection and use ISO 26000 as a proxy for corporate social responsibility.